Demographic characteristics differences of risk taking propensity among micro and small business owners in Malaysia - Fauzilah Salleh; Mohamed Dahlan Ibrahim (2011)
The purpose of this study is to investigate the differences between demographic characteristics and level of risk taking propensity of Malaysian MSEs owners. The study was conducted in the East Coast on business owners of small and medium business enterprises. A stratified sample totalling 260 names and addresses was taken from Small and Medium Industries Development Corporation (SME Corp). The Risk Attitudes Inventory (RAI) designed by Gene Calvert (1993) used in the survey to measure entrepreneurial risk taking propensity included a cover letter explaining the purpose of the study. The study concludes that there are no differences between risk taking propensity and business owners’ demographic characteristics such as gender, business owners’ age, education level and their business experience.